Analysis on Global Sea Turtle Conservation - Yu, Ziyi (Transactions on Environment, Energy and Earth Sciences, 2024)
Climate change is a major concern to sea turtle populations, notably in terms of temperature-dependent sex determination (TSD) and sea level rise. TSD is a biological mechanism that decides the sex of turtle hatchlings dependent on hatching temperature, and with global warming, sex ratios are becoming increasingly imbalanced. Furthermore, increasing sea levels endanger vital nesting locations, aggravating the threat to turtle populations. This article investigates these climate-related concerns while also looking at various habitat restoration strategies. Strategies such as collaborating with local fishermen and moving turtle eggs aim to reduce bycatch and poaching. Conservation measures are also thoroughly studied, with a focus on captive breeding and the ethical problems that come with it. Through public outreach, the rehabilitation center not only treats wounded turtles but also spreads awareness about turtle conservation. When considered collectively, these initiatives highlight the critical need for an integrated strategy to protect sea turtles from the growing stressors posed by their habitat. This project aims to investigate the challenges posed by climate change to sea turtles, as well as methods for protecting and restoring their environment. Ultimately, it will provide integrated solutions to guarantee the sea turtles' long-term existence.